Cheap and Commonplace: Making the Case for BCG and γδ T Cells in COVID-19 - Morrison, Alexandra L.; Sharpe, Sally; White, Andrew D.; Bodman-Smith, Mark (Frontiers in Immunology, 2021)
Antigen-specific vaccines developed for the COVID-19 pandemic demonstrate a remarkable achievement and are currently being used in high income countries with much success. However, new SARS-CoV-2 variants are threatening this success via mutations that lessen the efficacy of antigen-specific antibodies. One simple approach to assisting with this issue is focusing on strategies that build on the non-specific protection afforded by the innate immune response. The BCG vaccine has been shown to provide broad protection beyond tuberculosis disease, including against respiratory viruses, and ongoing studies are investigating its efficacy as a tool against SARS-CoV-2 (1). Gamma delta (γ𝛿) T cells, particularly the V𝛿2 subtype, undergo rapid expansion after BCG vaccination due to MHC-independent mechanisms. Consequently, γ𝛿 T cells can produce diverse defences against virally infected cells, including direct cytotoxicity, death receptor ligands, and pro-inflammatory cytokines. They can also assist in stimulating the adaptive immune system. BCG is affordable, commonplace and non-specific, and therefore could be a useful tool to initiate innate protection against new SARS-CoV-2 variants. However, considerations must also be made to BCG vaccine supply and the prioritization of countries where it is most needed to combat tuberculosis first and foremost.